Cross-Cultural Methodological Issues in Ethical Research - McDonald, Gael (Journal of business ethics, 2000)
Despite the fundamental and administrative difficulties associated with cross-cultural research the rewards are significant and, given an increasing trend toward globalisation, the move away from singular location studies to more comparative research is to be encouraged. In order to facilitate this research process it is imperative, however, that considerable attention is given to the methodological issues that can beset cross-cultural research, specifically as these issues relate to the primary domain or discipline of investigation, which in this instance is research on business ethics. Utilising the experience of a four country comparative study of both Asian and Western cultures in the field of business ethics, the following presents a discussion of methodological concerns under the three broad areas of operationalising culture, operationalising business ethics, and data interpretation.